Spatial-demographic Dimensions of Economic Composition in Nepal: Evidence from NPHC 2021 - Bohara, Pradeep Kumar; Raut, Rekha; Basnet, Kirti Bhushan (Baneshwor Campus Journal of Academia, 2025)
The intensive analysis of the economically active population of Nepal, conducted based on the 2021 National Population and Housing Census, reveals that the country has a primary sector-oriented national economy, the rules of which are associated with a rather high occupational segregation of the population according to sex and a high spatial inequality. Using a descriptive approach in analysing the secondary data of the National Statistics Office (NSO) of about 15 million people aged ten years or older, this paper will highlight the fact that Nepal highly depends on agriculture since it employs 57.3 % of the labour force. In this industry, women have an unrealistically high employment percentage (64.8 per cent women against 50.6 per cent men in employment), with the men working mostly in the construction and transportation sectors. The rural-urban divide also persists to define the labour force, 72.9 percent in the rural labour force is occupied with agriculture whereas it offers a more diversified image in the urban regions, with more high rates of participation in trade and services. This is despite the fact that even at the provincial level, there exists a colossal disparity between Kathmandu-based Bagmati having a capital and service economy on the one hand and Karnali / Sudur Paschim, which are largely agrarian based, on the other. Collectively, all these facts suggest that there is an urgency for strategic policies and measures to address the modernisation of agriculture, to create more off-farm job opportunities, to empower women so as to enable them to participate in higher-return activities and pave a path of sustainable and equitable growth trajectory in Nepal.